PENGARUH TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM BANK BCA DI BEI TAHUN 2023 - Tampubolon, Helena Ronauli; Sinaga, Stefie Fiorella; Saragi, Kurnya Suparto; Artono, Rikho Givson; Efrain Sinaga, Roy Alfonso; Hasugian, Christnova; Siallagan, Hamonangan (JURNAL ILMIAH EDUNOMIKA, 2025)
This quantitative study examines the significant impact of macro-economic factors, specifically inflation, exchange rates, and interest rates, on banking stock prices listed on the Indonesia Stock Exchange (IDX) between 2022 and 2023. The research aimed to investigate the individual and combined effects of these macro-economic factors on banking stock prices, providing valuable insights for investors and stakeholders. The study employed linear regression analysis, sampling 31 banking companies from the 47 listed on the IDX. This systematic approach ensured a comprehensive understanding of the relationships between the variables. This study underscores the significance of macro-economic factors in shaping banking stock prices. Investors, policymakers, and stakeholders must consider these factors to optimize investment strategies and mitigate potential risks.Keywords : inflation, exchange rates, interest rates, banking